A Review of Indigenous Employment Programs - Dockery, Alfred Michael; Milsom, Nicola (National Centre for Vocational Education Research (Australia), 2007)
Successive Australian governments over the last 20 years have focused on providing employment programs which support Indigenous people into their jobs. This report finds that the effectiveness of such programs has rarely been rigorously evaluated against their diverse objectives. It highlights a recent shift in policy toward strict employment outcomes, making programs easier to evaluate, but also cautions against applying the same 'mainstream' objectives to all Indigenous communities.